Response of Crop Yield and Productivity Contribution Rate to Long-Term Different Fertilization in Northeast of China - Xingzhu Ma; Xiaoyu Hao; Yue Zhao; Xinhua Peng; Jinghong Ji; Shuangquan Liu; Yu Zheng; Lei Sun; Baoku Zhou (Plants)
To reveal the changes in crop yield and contribution rate of black soil productivity under long-term different fertilization conditions in black soil areas and to find the important significance of fertilization for sustainable and stable crop yield, high yield, and improving the contribution rate of black soil nutrients. Based on the long-term experiment of black soil fertility in Harbin, the Ministry of Agriculture and Rural Affairs, under the maize–wheat–soybean rotation system, crop yield, sustainability and stability of yield, the contribution rate of black soil productivity, and natural nutrient supply capacity under 10 fertilization treatments (CK, NP, NK, PK, NPK, M, MNP, MNK, MPK, and MNPK) were analyzed. Results showed that, compared with the treatment of chemical fertilizer, yields of maize, wheat, and soybeans increased under treatment of organic fertilizer combined with chemical fertilizer, among which the yields of maize and wheat changed the most. As the rotation period lengthened, the sustainable yield index (SYI) values of chemical fertilizer treatment and its combination with organic fertilizer treatment gradually decreased. During the rotation period, the SYI value follows: chemical fertilizer combined with organic fertilizer > chemical fertilizer > organic fertilizer. The coefficient of variation (CV) of yield stability showed an overall trend of increasing first and then decreasing, with individual treatments showing a gradual increasing trend (NP and NPK; MNP and MNPK). Under different rotation periods, the overall contribution rate of soil productivity of long-term organic fertilizer combined with chemical fertilizer treatment was higher than that of single chemical fertilizer treatment. With the extension of the rotation period, the contribution rate of soil productivity of NPK treatment was higher and slightly increased, while other treatments showed a downward trend. Although the contribution rate of soil productivity of organic–inorganic fertilizer combined treatment (MNP and MNK) showed a downward trend, it still remained at a high level (97.2% and 95.9%). In addition, the black soil has strong phosphorus and potassium supply capacity; nitrogen was lower than those two elements, with an average natural potassium supply capacity of 94.0–97.1%. Therefore, the combination of organic and inorganic fertilizers is one of the most effective fertilization measures to stabilize crop yield in the black soil region. Nitrogen fertilizer, as a limiting factor for crop growth in the black soil region, should be emphasized in its application.